Voices from Those Not Heard: A Case Study on the Inclusion Experience of Adolescent Girls with Emotional–Behavioral Disabilities. Issue 1 (14th November 2018) - Whitlow, Darcie; Cooper, Robyn; Couvillon, Michael
Abstract: Research on inclusion for students with emotional–behavioral disabilities (EBD) has typically focused on male participants, because data are limited on female students who fit the criteria for having an EBD and are often misdiagnosed. This qualitative case study adds to the very limited research on the inclusion experiences of girls with EBD. Findings indicate that family dynamics and early traumas carry over into school environments, and that struggles with friendships in inclusive settings, inability to identify boundaries, a connection with one adult at school, and conflict with need for special education services were all part of the participants' experiences. The article concludes with a discussion of the implications for school social workers working and the need to focus on both individual and systems-level work in school settings for girls with EBD.